Restrukturisasi pendidikan kewarganegaraan sebagai langkah menghadapi era disrupsi - Nita Agustina Nurlaila Eka Erfiana; Ayok Ariyanto (Universitas Muhammadiyah Ponorogo, 2020)
This study aims to describe and analyze in-depth the restructuring of civic education as a step in facing the era of disruption. The presence of an era of increasingly massive disruption has prompted an overhaul of the concept of citizenship education learning in Indonesia, so that the delivery of civic education material remains relevant and the values and character of the nation are not eroded. Restructuring is one of the measures to rearrange and improve the civic education learning curriculum so that it is compatible with the increasingly rapid developments and advances in technology. The discussion on the new paradigm of civic education which contains three main dimensions of civic knowledge, civic skills, and civic deposition also needs to be reformulated, in order to answer problems related to the current development of the era of disruption. This study uses a qualitative-descriptive approach with critical discourse analysis methods and literature reviews from several comprehensive literature and journals. Based on the results of the study, it can be concluded that the presence of an era of disruption that has begun to erode the values and identity of the Indonesian nation needs to be overcome by increasing the understanding of nationality to citizens. One of them is by restructuring civic education. The restructuring is a process of rearranging or improving the formulation of a new paradigm that already exists in civic education by adapting these concepts to a wider area. It is hoped that with the restructuring of the content of citizenship education, the moral values of the nation will not be easily eroded by the presence of the era of disruption and instead become a reference for answering global problems.